Betulinic Acid Inhibits the Metastasis of Colon Cancer Cells through Regulating TGF-β/Smad Signaling Pathway - Xiaoying LIN; Aling SHEN; Meizhu WU; Ying CHENG; Xiaoping CHEN; Huixin LIU; Liya LIU; Zhiqing SHEN; Xiangyan WU; Nanhui XU; Jianfeng CHU; Youqin CHEN; et al. (康复学报)
Objective:To explore the effect of betulinic acid (BA) on the growth and metastasis of colon cancer cell line HCT116 and the underlying possible mechanism.Methods:HCT116 cells were cultured with McCoy's 5A medium containing 10%fetal bovine serum and 1%penicillin/streptomycin mixed solution in a 37℃,5%CO2incubator. HCT116 cells were seeded at a density of 0.2×105cells/mL in a 96-well plate and cultured overnight. Then the cells were treated with different concentrations (0,10,20, and 40 μmol/L) of BA for 24,48 and 72 h, respectively. And then CCK8 was added to detect its absorbance (A value) at 450 nm. HCT116 cells were seeded at a density of 0.4×105cells/mL in a 12-well plate and cultured overnight. The cells were then collected by digestion and centrifugation, and stained with trypan blue after treating with different concentrations (0,10,20, and 40 μmol/L) of BA for 48 h. The total number of cells was calculated by using a Countstar BioMed automatic cell counter. HCT116 cells were seeded at a density of 0.4×105cells/mL in a 12-well plate and cultured overnight. Then the cells were collected by digestion and centrifugation after treating with different concentrations (0,10,20, and 40 μmol/L) of BA for 48 h.1.0×105cells/mL cell suspension was used for the Transwell experiment of cell migration and invasion, respectively. The effects of different concentrations of BA intervention for 48 h on the migration and invasion ability of HCT116 were analyzed. Western blot was used to detect the effect of BA on the protein expression of TGF-β and Smad2/3 in HCT116 cells after treated with BA for 48 h.Results:(1) CCK8 assay showed that the cell viability in each group was significantly reduced after treatment with different concentrations of BA for 24,48 and 72 h, and the differences were statistically significant compared with the 0 μmol/L group respectively (P<0.05); The cell count results showed the number of cells in each group was remarkably decreased, and the differences were statistically significant compared with the 0 μmol/L group respectively (P<0.05). (2) Transwell assay showed that the number of cells that migrated or invaded into the membrane was profoundly inhibited in each group after treatment with different concentrations of BA for 48 h, and the differences were statistically significant compared with the 0 μmol/L group respectively (P<0.05). (3) Western blot assay showed that the protein expression of TGF-β and Smad2/3 was obviously decreased in each group after treated with different concentrations of BA for 48 h compared with the 0 μmol/L group.Conclusion:BA can inhibit the growth and metastasis of colon cancer cells, and its mechanism may be achived by regulating the TGF-β/Smad signaling pathway.